Resources and their impact on the effectiveness of processes which shape dynamic capabilities of Polish enterprises = Wpływ zasobów na efektywność procesów kształtowania dynamicznych zdolności polskich przedsiębiorstw - Cyfert, Szymon; Krzakiewicz, Kazimierz (Zielona Góra: Faculty of Economics and Management Press)
The purpose of this article is to discuss the results of our research into how different resources impact the effectiveness of dynamic capabilities processes in Polish businesses. As a starting point, the article characterises the nature and character of dynamic capabilities in Polish firms as well as highlighting the significance of different resources in developing those capabilities. On that basis conclusions are offered regarding the relationship between those resources and the effectiveness of capabilities-shaping processes.
Keywords: przedsiębiorstwa polskie; zdolności dynamiczne; kształtowanie zdolności; efektywność; zasoby; Polish enterprises; dynamic capabilities; resources; effectiveness